Formation of nitrides and carbides on titanium alloy surface through EDM - Mohammed , Baba Ndaliman; Khan, Ahsan Ali; Ali, Mohammad Yeakub (Trans Tech Publications, Switzerland, 2012)
In this investigation, electrical discharge machining (EDM) was done with Cu-TaC powder metallurgy (PM) electrode and urea solution dielectric fluid. The main objective is to improve the surface wear property of Ti-6Al-4V alloy through the formation of hard ceramic compounds on its surface during EDM. The experiments were conducted with peak current, Ip (3.5,5.5 A) and pulse duration, ton (3.3, 5.3 μsec) as the machining variables. The outputs investigated are surface characteristics and micro-hardness. The formation of nitrides, carbides and oxides of tantalum and titanium on the EDMed surface was confirmed. The highest micro-hardness of 902.2 Hv was obtained with Ip of 5.5 A and ton of 3.3 μsec.